Synthesis of an ABA triblock copolymer of poly(DL-lactide) and poly(ethylene glycol) and blends with poly(epsilon-caprolactone) as a promising material for biomedical application - (:unkn) unknown (AMER CHEMICAL SOC, 2005)
The aim of this work was preparation of blends based on ABA triblock copolymers [A=poly(DL-lactide); B=poly(ethylene glycol)] and poly(epsilon-caprolactone) (PCL), their characterization, hydrolytic degradation study, and evaluation of the possibility to use these materials in tissue engineering. GPC, FTIR, H-1 NMR and DSC analyses were used for block copolymers characterization, and the corresponding blends with PCL, were characterized by FTIP, TGA, DSC and contact angle measurements. Porous films were prepared from triblock copolymers, and corresponding blends using solvent casting particulate-leaching technique. Hydrolytic in vitro degradation was performed in phosphate buffer solution. Preliminary cell growth experiments, using L929 mouse fibroblasts, were performed to observe the attachment and growth of cells on polymer matrices.
Keywords: DRUG-RELEASE; DEGRADATION; BEHAVIOR; ACID